Application of K-Means Clustering for Designing Power Distribution Network - Bansal, Shilpa; Neha Gupta; Vadhera, Shelly (Asian Journal of Electrical Sciences, 2019)
Installation of independent power distribution network with central generation using solar power plant is a trending solution to meet the demands of electricity of energy starved rural areas. In this paper, application of K-means clustering is proposed for designing power distribution network which segregates the houses in suitable number of clusters and all the clusters centroids are connected to the central location of solar power plant. Total number of clusters is selected by application of three methods like Elbow method, CH index method and Average Silhouette method. This paper can act as a useful tool for planning and designing the distribution network while optimizing the distribution losses and installation cost of the network.